Freezing of Lakes and the Evolution of their Ice Cover - Leppäranta, Matti (Springer, 2015)
A large number of boreal lakes are ice-covered in winter. However, research and literature of these lakes concerns by far only the open water season. In particular, no textbook on physics of ice-covered lakes exists, and now it would be a proper time to prepare such. Winter limnology has become an increasing active field of research recently. A series of winter limnology symposia was started in 2008 in Finland with nearly 100 participants. The second symposium was held in Berlin in 2010 and the third one is coming in 2012 in Norway. Winter limnologists need strongly a textbook on lake ice physics since the ice acts as their boundary condition.